Clinical utility of nitisinone for the treatment of hereditary tyrosinemia type-1 (HT-1) - Das, Anibh Martin (Appl Clin Genet, 2017)
Medical therapy for hereditary hepatorenal tyrosinemia (hereditary tyrosinemia type 1, HT-1) with nitisinone was discovered incidentally, and is a by-product of agrochemistry. It blocks the catabolic pathway of tyrosine, thereby leading to a reduction in the accumulation of toxic metabolites in HT-1. It has to be combined with a low-protein diet supplemented with amino acid mixtures devoid of tyrosine and phenylalanine. This treatment option has completely changed the clinical course of patients suffering from HT-1 who used to die in the first few months to years of life from liver failure, renal dysfunction, and/or hepatocellular carcinoma (HCC). It is essential to start nitisinone therapy early in life to avoid sequelae; beginning treatment in the newborn period is ideal. As initial clinical symptoms of HT-1 are often atypical and because there is a clinically latent phase during the first few months of life in many patients, newborn screening is required to secure early diagnosis. Succinylacetone in blood is a reliable screening parameter whereas tyrosine is neither specific nor sensitive. Especially HCC, but also liver and kidney dysfunction, rickets, and neurological crises can be prevented in most patients if nitisinone therapy is started in the newborn period. It is essential to adhere to a low-protein diet to avoid tyrosine toxicity. Reversible eye symptoms may occur as a side-effect of nitisinone, but other side effects are rare. Neurocognitive development is impaired in some patients, and the reason for this is unclear. Metabolic monitoring includes measurement of tyrosine, succinylacetone, and nitisinone concentrations in blood.